2018
DOI: 10.1029/2018ms001301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Explicit Convection on Land Surface Air Temperature and Land‐Atmosphere Coupling in the Thermal Feedback Pathway

Abstract: Simulating and understanding continental temperature extremes is a critical issue in Earth System Modeling. Conventional general circulation models are impaired by imperfect cloud and boundary layer parameterization schemes with implications for potentially unrealistic distributions of atmospheric variables and land-atmosphere coupling signals. In this study we examine a modern version of Superparameterization (SP) in the Community Atmosphere Model v.5 to examine impacts of SP on the characteristics of land su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The superparameterisation uses a simple fixed conversion rate (see Khairoutdinov and Randall, 2003, Appendix D), whereas the cloud scheme uses the formulation of Beheng (1994). Focusing on this aspect, Suzuki et al (2015) has shown that the distribution of precipitation categories (non-precipitating, drizzle, rain) is dependent on its expression, thereby influencing the precipitation rate. Future studies with SP-EMAC should investigate the onset of precipitation for maritime clouds in more detail or should consider using a two-moment microphysical scheme and its coupling to an aerosol submodel.…”
Section: Influence On Regional Aspectsmentioning
confidence: 99%
“…The superparameterisation uses a simple fixed conversion rate (see Khairoutdinov and Randall, 2003, Appendix D), whereas the cloud scheme uses the formulation of Beheng (1994). Focusing on this aspect, Suzuki et al (2015) has shown that the distribution of precipitation categories (non-precipitating, drizzle, rain) is dependent on its expression, thereby influencing the precipitation rate. Future studies with SP-EMAC should investigate the onset of precipitation for maritime clouds in more detail or should consider using a two-moment microphysical scheme and its coupling to an aerosol submodel.…”
Section: Influence On Regional Aspectsmentioning
confidence: 99%
“…The motivation is multiple: First and foremost, CPMs can improve the simulations of MCSs and other precipitation (Berg et al., 2015; Feng et al., 2018, 2019; Prein et al., 2017a, 2021; Q. Yang et al., 2017). Furthermore, convection‐permitting capabilities, either conventional (Dai et al., 2021) or through cloud super‐parameterization with embedded cloud‐resolving models (Qin et al., 2018; Sun & Pritchard, 2016, 2018), improve representations of land‐atmosphere coupling over well‐known hotspot regions like the US Great Plains (Koster et al., 2004). Given these improvements, one may surmise that CPMs would improve surface climate representation over Central US during summertime.…”
Section: Introductionmentioning
confidence: 99%
“…From the technical perspective, the coupling strength is influenced by the choice of the data set used for the investigation (Dirmeyer et al, 2018;Ferguson and Wood, 2011) and, in case of models, their configuration such as parameterization schemes (Chen et al, 2017;Milovac et al, 2016;Pitman et al, 2009), initialization (Santanello Jr. et al, 2019) or model resolution (Hohenegger et al, 2009;Knist et al, 2020;J. Sun & Pritchard, 2018;Jian Sun & Pritchard, 2016;Taylor et al, 2013).…”
Section: Introductionmentioning
confidence: 99%